2011
DOI: 10.1007/s00268-011-1167-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stroke During Surgery for Carotid Body Tumors

Abstract: Internal carotid artery manipulation, including reconstruction, ligation, and repair of injury, significantly increased the incidence of stroke. For uncomplicated CBT resection, careful preoperative planning, especially for patients with class II and III tumors, is mandatory to avoid inadvertent ICA manipulation necessitated by bleeding. Early ECA division during the operation rather than preoperative percutaneous embolization in patients with class II and III tumors was significantly effective in reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In a small study population, the Dardik et al multivariate analysis demonstrated that tumor size, and not Shamblin classification, predicts cranial nerve injury. On the other hand, Lim et al and Power et al showed that patients with advanced Shamblin classification had a higher risk of neurovascular complications, and Gwon et al found that the Shamblin classification was significantly related to the incidence of stroke ( p = .041) and that tumor size was not ( p = .412). Therefore, a review of these conflicting data inevitably leads to the conclusion that larger scale studies are necessary in order to confirm the correlation between tumor size and Shamblin classification and the development of postoperative neurovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study population, the Dardik et al multivariate analysis demonstrated that tumor size, and not Shamblin classification, predicts cranial nerve injury. On the other hand, Lim et al and Power et al showed that patients with advanced Shamblin classification had a higher risk of neurovascular complications, and Gwon et al found that the Shamblin classification was significantly related to the incidence of stroke ( p = .041) and that tumor size was not ( p = .412). Therefore, a review of these conflicting data inevitably leads to the conclusion that larger scale studies are necessary in order to confirm the correlation between tumor size and Shamblin classification and the development of postoperative neurovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 5 in 2001 with 30 patients showed 0% stroke rates, unfortunately the Shamblin classification is unknown in these patients. Gwon et al 6 showed a 25% risk of stroke with 15 patients, 75% of the strokes were Shamblin III. Plukker et al 7 showed an 8% stroke risk, all strokes were Shamblin III.…”
Section: Discussionmentioning
confidence: 96%
“…Of the studies reviewed, the higher the Shamblin classification, the higher the risks of stroke 6 7. A review of 15 patients with Shamblin III found higher risks of postoperative neurovascular complications 8.…”
Section: Discussionmentioning
confidence: 99%
“…should be used only to perform superselective embolization with the aim of preoperative tumor shrinking, reducing vascularisation and intraoperative bleeding (11,13,14). Preoperative embolization is suggested in high risk tumors (group 2 and 3) (11,12) and also in our series 2 patients (1 from group 2 and 1 from group 3) underwent the procedure because of CT evidence of vagus nerve encasement.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%